Muji Brand Image and Buying Decision of Consumers in Bangkok and Suburban Area through Integrated Marketing Communication Strategy in Discount Pricing - Sakuna, Chachaya; Chimjinda, Supitcha (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
The objective of the research is to study Muji Brand Image and Buying Decision of Consumers in Bangkok and Suburban Area through Integrated Marketing Communication (IMC) Strategy in Discount Pricing, using questionnaire as a tool for data collection in this quantitative research. The result revealed that most of the samples were 18 – 23 years old with bachelor’s degree. They were school and university students with the average income of 10,0001 – 20,000 baht per month. According to Muji brand image through IMC strategy in discount pricing, it showed that the overall opinion of respondents toward Muji brand image through IMC strategy in discount pricing was high in level, however, when considering thoroughly, personality dimension was the highest level, following by value dimension and user dimension, respectively. Regarding to buying decision through IMC in Discount Pricing, it was found that IMC strategy in discount pricing effected on buying decision of the research samples at highest level, however, when considering thoroughly, it showed that their buying decision was high in level in purchase decision stage, following by need recognition stage and evaluation of alternatives stage, respectively.